An enhanced calibration of a recently released megatree for the analysis of phylogenetic diversity - Gastauer,M. (2016)
Abstract Dated or calibrated phylogenetic trees, in which branch lengths correspond to evolutionary divergence times between nodes, are important requirements for computing measures of phylogenetic diversity or phylogenetic community structure. The increasing knowledge about the diversification and evolutionary divergence times of vascular plants requires a revision of the age estimates used for the calibration of phylogenetic trees by the bladj algorithm of the Phylocom 4.2 package. Comparing the recently released megatree R20120829.new with two calibrated vascular plant phylogenies provided in the literature, we found 242 corresponding nodes. We modified the megatree (R20120829mod.new), inserting names for all corresponding nodes. Furthermore, we provide files containing age estimates from both sources for the updated calibration of R20120829mod.new. Applying these files consistently in analyses of phylogenetic community structure or diversity serves to avoid erroneous measures and ecological misinterpretation.